2018
DOI: 10.1073/pnas.1716973115
|View full text |Cite
|
Sign up to set email alerts
|

In vivo repressed genes of Vibrio cholerae reveal inverse requirements of an H + /Cl transporter along the gastrointestinal passage

Abstract: SignificanceBacterial infection is still a global threat to human health. Gene expression profiling of pathogenic bacteria during infection may aid in a better understanding of the pathophysiological events. Here, we present a reporter-based technology to identify in vivo repressed (ivr) genes of Vibrio cholerae. Our data demonstrate that constitutive expression of ivr genes reduces colonization fitness, indicating a pivotal role of gene silencing. A comprehensive characterization of an H+/Cl− transporter reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 60 publications
1
44
0
Order By: Relevance
“…For example, upon infection, V . cholerae senses host signals and is able to coordinate both virulence gene activation and repression to evade host defenses and successfully colonize intestines [ 2 5 ]. Late in the infection, V .…”
Section: Introductionmentioning
confidence: 99%
“…For example, upon infection, V . cholerae senses host signals and is able to coordinate both virulence gene activation and repression to evade host defenses and successfully colonize intestines [ 2 5 ]. Late in the infection, V .…”
Section: Introductionmentioning
confidence: 99%
“…environmental changes, including changes in nutrient availability, osmolarity, temperature, and pH. There is an array of regulatory systems controlling these adaptive responses during V. cholerae infection (10)(11)(12)(13). Early in infection, V. cholerae genes involved in the acid tolerance response (ATR) are induced as the cells pass through the acidic environment of the stomach (14).…”
mentioning
confidence: 99%
“…Early in infection, V. cholerae genes involved in the acid tolerance response (ATR) are induced as the cells pass through the acidic environment of the stomach (14). After exiting the stomach, V. cholerae adapts to the more alkaline environment in the small intestine by repressing ATR genes; a failure to do so results in an intestinal colonization defect (13). At the same time, V. cholerae activates the expression of genes required for colonization and disease development (i.e., the ToxR regulon).…”
mentioning
confidence: 99%
“…Thus, this pathogen very efficiently combines its responses to host stimuli in order to simultaneously upregulated factors necessary for colonization (ctx and tcp genes), while using these same factors to transcriptionally repress the biogenesis of anti-colonization factors such as MSHA. Recently, another study used a different approach to identify in vivo-repressed genes in V. cholerae and found that clcA, encoding an H + /Cl − transporter, is repressed during infection [132]. While ClcA facilitates survival under low pH (e.g., the stomach), its activity becomes detrimental under the alkaline conditions found in the small intestine; indeed, constitutive expression of clcA reduces colonization fitness.…”
Section: In Vivo Repressed Genesmentioning
confidence: 99%